RECENT ADVANCES IN NANO SPONGE TECHNOLOGY: FROM SYNTHESIS TO APPLICATIONS - DEEPIKA; TYAGI, YOGITA; MORRIS, SRISHTI; KORI, ARTI (International Journal of Applied Pharmaceutics, 2026)
Nanosponges (NSs) are an emerging class of advanced nanomaterials with wide-ranging applications in healthcare, environmental protection, catalysis, and sensing. Composed of polymers, inorganic compounds, or hybrid structures, they possess a large surface area, adjustable pore size, and tunable chemical properties, allowing precise adaptation to various environments. These features make them highly effective for drug delivery, pollutant adsorption, and catalytic processes. Notably, NSs exhibit exceptional drug loading efficiencies, reaching up to 98%, such as 95% for cyclodextrin-based formulations encapsulating the anticancer drug doxorubicin. Their enhanced performance is primarily due to their porous network and ability to form stable inclusion complexes with hydrophobic molecules. In environmental applications, mesoporous silica NSs have shown high efficacy in removing toxic heavy metals like chromium (VI) and lead (II) from wastewater. To achieve optimal performance, several advanced characterization techniques are employed. In Situ transmission electron microscopy (TEM) allows real-time visualization of structural evolution, while X-ray diffraction (XRD) provides data on crystallinity and phase transitions. Dynamic light scattering (DLS) determines particle size distribution and stability, and Zeta Potential Analysis assesses surface charge interactions. Moreover, fourier transform infrared (FT-IR) Spectroscopy identifies chemical bonding and drug–carrier interactions, whereas thermogravimetric analysis (TGA) provides insights into thermal stability and composition. Ongoing research continues to refine the synthesis, functionalization, and application of nano sponges, enabling the development of more efficient, sustainable, and multifunctional nanostructures that address critical challenges in medicine, environmental remediation, and advanced materials science.